Between impunity and justice?: Exploring stakeholders’ perceptions of Colombia’s special sanctions (sanciones propias) for international crimes - Mayans-Hermida, Beatriz E. (International journal of transitional justice, 2023)
The peace agreement signed by the Colombian government and the FARC has an innovative sanctioning regime which, based on a restorative approach, offers non-custodial sanctions as a less punitive form of punishment for international crimes. However, given their leniency, these ‘special sanctions’ have caused controversy. Based on qualitative interviews, this study explores the perceptions of different stakeholders concerning various issues related to the special sanctions’ nature, goals, processes, (envisioned) outcomes and challenges. Our findings reveal that most participants perceive these sanctions as a tool that can modestly help repair the damage done, reintegrate (certain) offenders into society, and promote coexistence. Only a limited number of respondents saw these sanctions as punishment. For several participants, the special sanctions may be an alternative accountability measure to prison. However, this seems to depend on meeting certain preconditions, victims’ participation, the type of crime and the offender’s rank and affiliation.